Pogrzeb kartofla . The Burial of a Potato - Kolski, Jan Jakub (Studio Filmowe im Karola Irzykowskiego, 1990)
Duration: 01:36:00 Set in 1946, the film tells the story of a Polish villager returning home after years in a concentration camp. Mateusz is an old-timer, a saddler, who finds nothing but hostility when he makes it home after years away. He is not a Jew, though the villagers brand him one and give him a hard time. They have already taken his property; now they feel guilty about the death of his son at the end of the war, and do not want the father around. In the background we see the beginning of the communist takeover in Poland, but this is not the major focus of the film. Rather, it is Mateusz's struggle to fit in. Kolski, pace national-Catholic literature and film, presents the villagers as superficially religious brutal antisemites.